Políticas públicas educacionais e a escolarização do estudante surdo em um contexto de uma Escola Municipal de Anápolis-GO - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
This work is linked to Research Line 1 - Education, School, and Technologies of the Interdisciplinary Postgraduate Program in Education, Language, and Technologies (PPG-IELT) at the State University of Goiás – UEG. Inclusive educational public policies ensure bilingual education for deaf students through the organization of bilingual schools and classes, as well as inclusive schools. The problem explored in this research is: how do current educational public policies enable quality education and promote social and pedagogical development for deaf students in the municipal education system in Anápolis? The general objective was to analyze educational public policies and the education of deaf students in the context of a municipal school in Anápolis-GO. The research is qualitative, using bibliographic, documentary, and field research procedures. It aligns with the phenomenological research conception in addressing its processes and approaches. For theoretical foundation, researchers/authors were employed who support this work and contribute in the following areas: Educational Public Policies and guidelines for inclusive teaching - Reis (2013), Souza (2018), Mantoan (2017); Bilingual education for the deaf - Strobel (2018); Lacerda (2012) Quadros (2006); Continuing education for bilingual inclusive education – Gatti and Barreto (2009), André (2016); Pedagogical practices of bilingual inclusive education and Specialized Educational Assistance - Mantoan (2007), Damázio (2007), Lacerda (2007); Educational Interpreter of Brazilian Sign Language - Capovila (2011), Quadros (2005), among others who were fundamental to the construction of this research, contributing to the understanding process in theory and practice. For the field research, semi-structured interviews were conducted with 4 participants, including two regular teachers, a teacher of Specialized Educational Assistance (SEA), and a Brazilian Sign Language (Libras) interpreter in a municipal school in Anápolis - GO. Regarding data analysis, dialectical hermeneutics was used, as this type of research deals with meanings, motives, aspirations, beliefs, and attitudes (Minayo, 2010). The data were organized around three central axes: Educational Public Policies and guidelines for inclusive teaching in the municipal education system; continuing education from the perspective of bilingual inclusive education, emphasizing the use of Libras as the legal means of communication for deaf students; pedagogical practices of inclusive and bilingual education developed in the school environment. The results indicated that inclusive educational public policies for deaf students should be based on the valorization of bilingual education, understanding Libras as a visual-spatial language to facilitate the learning of these students. Furthermore, it revealed the need for collaborative work, with an inclusive approach built in practices, connecting school teams with various actions and planning, rethinking continuing education more deeply considering the educational process that encompasses the student's deafness nuances and the peculiarities of bilingual inclusive education.
Public educational policies and the schooling of deaf students in the context of a Municipal School in Anápolis-GO
Keywords: Políticas Públicas Educacionais - Inclusão; Inclusão - Estudante surdo; Políticas Públicas Educacionais - Escola inclusiva bilíngue; CIENCIAS HUMANAS::EDUCACAO